Pengaruh Kurs dan Inflasi terhadap Pertumbuhan Laba pada Pt. Bank Central Asia Syariah Tbk, Periode Tahun 2012-2019 - Yulianta Yulianta; Nurjaya Nurjaya (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of exchange rates and inflation on the profit development of PT BCA Syariah Tbk, which is listed on the Indonesia Stock Exchange in the 2012-2019 period. The independent variable in this study is the exchange rate (X1), inflation (X2) and the dependent variable is the profit growth of PT BCA Syariah Tbk (Y). The type of research used is quantitative research by taking all time series data covering the exchange rate, inflation and profit growth of PT BCA Syariah Tbk, for the period 2012 to 2019. The number of research samples using saturated sampling techniques was obtained as many as 96 samples. The data analysis used is multiple linear regression analysis using IBM SPSS 25.0. The results of this study indicate that the exchange rate variable has a significant effect on PT BCA's profit growth with a significant value of 0.020 (<0.05) and the inflation variable has no effect on PT BCA's profit growth with a significant value of 0.608 (> 0.05) with a standard degree of validity of 95. %. The coefficient of determination (R2) is 0.306%, which means that the independent variable affects the dependent variable by 30.6,% and the remaining 69.4% is influenced by other variables outside of this study. The results of the F test show that the independent variables exchange rate and inflation simultaneously have a significant effect on profit growth of PT BCA Syariah Tbk. The t test results show that the exchange rate variable partially has a significant effect on the profit growth of PT BCA Syariah Tbk. The inflation variable has no significant effect on stock prices on the profit growth of PT BCA Syariah Tbk.